The influence of organisational support, transactive memory system and information technology competencies for facilitating knowledge transfer in enterprise resource planning success - Muallah, Nur Izzah (2019)
The successes of the ERP system in an organisation depend on knowledge transfer activities made and the effectiveness of the transferred knowledge between the parties involved. It is crucial to determine a set of knowledge transfer activities that need to do besides the efforts taken by the organisation in ensuring ERP success. Currently, there is still a lack of standard knowledge transfer measurement and empirical study on the impact of organisational support towards ERP system success, especially from the context of food manufacturing. Previous research has reported various factors impacted the transfer of knowledge in strategic alliances and joint venture. Nonetheless, organisational support is the least factor mentioned, especially studies from Malaysia. For bridging the gap, two theories employed, Knowledge-Based View (KBV) theory and Organisational Learning Theory (OLT) as the fundamental theories to observe the phenomenon and further incorporate with measurement theories. The main purpose of this study is to empirically validate the KT model with three main factors that influenced the ERP success, specifically for food manufacturing in Malaysia. The study developed a Knowledge Transfer (KT) validated measurement scale based on rigorous steps to increase the reliability and validity values. A total of 56 respondents have responded to the survey from 65 companies that yield 86 per cent response rate. The respondents were selected from the executive level and above from large food manufacturing in Malaysia. Five hypotheses were accepted. The study highlighted that IT Infrastructure (0.304) is found as the most influential factors while Communication (-0.093) and Retrieval (-0.110) factors were insignificant factors that affect KT activities towards ERP success. From the results, it concluded that organisation with better infrastructure leads to increasing rates of ERP success. The proposed infrastructure is any customised system application that helps organisations stay successful in their business. However, the inability to deliver a clear message in the organisation through communication and lack of retrieval practices in Transactive Memory System (TMS) has affected the overall ERP success level whereby the current level is moderate. Therefore, based on the result, it is clear that having the correct system is very helpful in achieving ERP success in an organisation.